Improving hand function after spinal cord injury. (January 2022) - Fridén, Jan; House, James; Keith, Michael; Schibli, Silvia; van Zyl, Natasha
Nerve transfer surgery has expanded reconstructive options for restoring upper extremity function following spinal cord injury. By adding new motor donors to the pool already available through tendon transfers, the effectiveness of treatment should improve. Planning which procedures and in which order to perform, along with their details must be delineated. To meet these demands, refined diagnostics are needed, along with awareness of the remaining challenges to restore intrinsic muscle function and to address spasticity and its consequences. This article summaries recent advances in surgical reanimation of upper extremity motor control, together with an overview of the development of neuro-prosthetic and neuromodulation techniques to modify recovery or substitute for functional losses after spinal cord injuries.